Biosynthesis and Functional Significance of Peripheral Node Addressin in Cancer-Associated TLO - Weinstein, Aliyah M.; Storkus, Walter J. (Frontiers in Immunology, 2016)
Peripheral node addressin (PNAd) marks high endothelial venules (HEV), which are crucial for the recruitment of lymphocytes into lymphoid organs in non-mucosal tissue sites. PNAd is a sulfated and fucosylated glycoprotein recognized by the prototypic monoclonal antibody MECA-79. PNAd is the ligand for L-selectin, which is expressed on the surface of naïve and central memory T cells, where it mediates leukocyte rolling on vascular endothelial surfaces. Although PNAd was first identified in the HEV of peripheral lymph nodes, recent work suggests a critical role for PNAd in the context of chronic inflammatory diseases, where it can be used as a marker for the formation of tertiary lymphoid organs (TLO). TLO form in tissues affected by sustained inflammation, such as the tumor microenvironment (TME), where they function as local sites of adaptive immune cell priming. This allows for specific B- and T-cell responses to be initiated or reactivated in inflamed tissues without dependency on secondary lymphoid organs (SLO). Recent studies of cancer in mice and humans have identified PNAd as a biomarker of improved disease prognosis, and blockade of PNAd or its ligand, L-selectin, abrogates protective anti-tumor immunity in murine models. This review examines pathways regulating PNAd biosynthesis by the endothelial cells integral to HEV and the formation and maintenance of lymphoid structures throughout the body, particularly in the setting of cancer.